Characterization and optical properties of bismuth chalcogenide films prepared by pulsed laser deposition technique. (January 2017) - Adam, A.M.; Lilov, E.; Lilova, V.; Petkov, P.
Abstract: Thin films of Bi-based chalcogenides were prepared by pulsed laser deposition (PLD) technique according to the stoichiometric formula: Bi2 (Se1−x Tex )3 . Their optical properties were studied aiming to find the suitable area of application and the optimum composition amongst the samples under study. X-ray diffraction analysis proved the crystallinity of the deposited samples; in addition, surface roughness and films homogeneity were studied by atomic force microscopy (AFM) confirming the suitability of PLD technique to prepare homogenous and smooth films of the concerned alloys. Absorption coefficient calculations showed higher absorption values of 5×10 5 and 6×10 5 cm −1 for Te contents of 90% and 100% in the Bi2 (Se1−x Tex )3 system respectively. Optical band gap of the concerned films were calculated and found to be in the range of 0.76–1.11 eV, exhibiting comparable values with the previously reported by other authors. Optical studies conformed direct and allowed transitions in all films. Refractive index (n) and dielectric constants (Ɛr ) and (Ɛi ) were calculated and studied as a function of the wavelength. Values and behavior of (n), (Ɛr ) and (Ɛi ) indicated strong dependence on the composition and the wavelength range.